Associated factors to attitudes and perceptions toward HIV/AIDS: a study of ethnic minorities in Buon Ma Thuot City, Dak Lak Province, Vietnam - Hoang, Thang Nghia; Pham, Duoc Tho (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Background: In Central Highland of Vietnam, number of HIV infected people in the Highlands region was 2,869, with 654 cases of AIDS. There are very few researches on HIV/AIDS, especially, research in community. The ethnic minority populations are the source of differences from other regions of in the country. Negative attitude and misperception toward HIV/AIDS are remaining among this group.Aims: This study aims to illustrate attitude and perception towards HIV/AIDS among ethnic minority in Buon Ma Thuot City and determine factors related to attitude and perception towards HIV/AIDS in this population.Methods: We performed a cross-sectional survey of collected from 810 ethnic minority aged 15-49 in Buon Ma Thuot city, Vietnam in 2012. Face-to-face interviews were conducted to collect information regarding HIV knowledge, HIV perception and attitude towards people living with HIV/AIDS (PLWHA). The mean score was calculated. Multivariate analysis performed to analyze the influence of socio-demographic, HIV information sources and HIV knowledge on attitudes and perception towards HIV/AIDS.Results: We identified that the mass media channel has been used as HIV information resource (92.8%); however, the respondents received HIV information through mass media channels had lower perception and attitude towards HIV/AIDS. The multivariate analysis showed that the socioeconomic-demographic characteristic, HIV information, and HIV knowledge significantly associated with perception and attitude towards HIV/AIDS. The findings highligh the HIV information provided by health officers, who are ethnic minorities, had more effectiveness of improving attitude towards People living with HIV/AIDS (PLWHA) in the premise community (p<0.05).Conclusion: Based on these data, we recommend improving quality of HIV message through mass media channel with adequate HIV information combine with social messages. Besides, combination of the role of multichannel mass media and health officers is needed to improve the perception and attitude towards HIV/AIDS among Ethnic minorities. Submitted: 9 October 2017, Accepted: 28 October 2017. DOI: https://doi.org/10.35898/ghmj-12103